Cognitive disorganization in hippocampus: a physiological model of the disorganization in psychosis - Olypher, Andrey V; Klement, Daniel; Fenton, André A (The Journal of neuroscience, 2006)
Cognitive coordination refers to processes that organize the timing of activity among neurons without altering individual discharge properties. Coordinating processes allow neural networks to coactivate related representations and prevent the coactivation of unrelated representations. Impaired cognitive coordination, also called cognitive disorganization, is hypothesized to be the core deficit in the disorganized syndrome of schizophrenia (Phillips and Silverstein, 2003), a condition characterized by hallucinations, disorganization, and thought disorder. This disorganization hypothesis is based on the observation that schizophrenic subjects are impaired at segregating relevant and irrelevant stimuli and selectively using associations between relevant cues. We report that injecting the neural activity blocker tetrodotoxin (TTX) into one hippocampus persistently coactivated pyramidal cells in the uninjected hippocampus that initially discharged independently. In accord with the definition of cognitive disorganization, pyramidal cell firing rates only changed for 15 min and did not accompany the coactivation. The TTX-induced coactivity was maximal at gamma periods, consistent with altered gamma oscillations and disorganization in schizophrenia. A network model confirmed that increasing the coupling of weakly associated cells impairs the selective activation and inhibition of stored spatial representations. This TTX-induced cognitive disorganization correctly predicted that the same TTX injection selectively impaired the ability of rats to segregate relevant associations among distal spatial stimuli from irrelevant local stimuli (Wesierska et al., 2005). The TTX-induced coactivity of hippocampal pyramidal cell discharge has construct and predictive validity as a physiological model of psychosis-related disorganization.
Keywords: Disease Models, Animal; Psychotic Disorders; modely nemocí na zvířatech; krysa rodu Rattus; Hippocampus; Tetrodotoxin; kognitivní poruchy; tetrodotoxin; akční potenciály; Action Potentials; Animals; zvířata; Cognition Disorders; psychotické poruchy; hipokampus; Rats